Pengaruh Kualitas Pelayanan Terhadap Kepuasan (Studi Pada Poliklinik RSUD Dok II Jayapura) - Kadun MT, Alienra Davry Nanda; Nurjaman, Rahmat (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
Health services in Papua face several challenges, especially in service quality. The only and highest referral hospital in the entire Papua region is RSUD Dok II Jayapura. This quantitative research seeks to prove the influence of service quality (X) on patient satisfaction (Y). The research sample comprised 95 patients selected based on the incidental sampling method. Data was analyzed using multiple linear regression techniques to prove the simultaneous and partial influence of service quality variables (physical evidence, guarantee, responsiveness, empathy, and reliability) on satisfaction. Before the regression test, a classical assumption test was carried out to test the data's normality, multicollinearity, and heteroscedasticity. The research results explain the significant simultaneous influence of service quality on satisfaction. Partially, the variables empathy (X4) and reliability (X5) have a substantial effect on satisfaction (Y). Meanwhile, the variables physical evidence (X1), guarantee (X2), and responsiveness (X3) were found not to influence satisfaction (Y).